Treatment of Pathologic Fracture of the Humeral Diaphysis Using Metal andPolymer Express Endoprosthetic Replacement as an Example of the Accelerated Rehabilitation of Cancer Patients - A. K. Antonov; V. M. Kochemasov; A. V. Filimonyuk-Smelkov; D. S. Mekhtikhanov; A. A. Antonov; K. A. Antonov; V. G. Yagubov (Неотложная медицинская помощь, 2020)
ABSTRACT. We report a case of treatment of a 60-year-old female patient D. with a metastatic fracture of the upper and middle third of the left humerus. We made a radical removal of the metastasis, which was complicated by pathological fracture of the left humerus. To replace the removed tumor defect we performed metal and polymer endoprosthetic replacement of the left humeral diaphysis using a locking screw system and bone cement (methyl methacrylate). For accelerated recovery and rehabilitation we applied adaptogenic immunomodulator «Vitavis» (Altai elixir) and neutral anolyte (NA). After the removal of the tumor, postoperative wound was treated with neutral anolyte (NA). Dressings also contained neutral anolyte (NA). These drugs were successfully combined with postoperative basic therapy. The patient was discharged from the hospital on the 4th day after surgery. The functional results of the left upper limb are satisfactory.